Utilização de aditivos na ensilagem de cana-de-açúcar - Freitas, Fernanda Mara Cunha (2013)
The objective of this work was to evaluate the fermentation characteristics of silage of sugarcane mixed with soybean hulls, bacterial inoculant (L. buchneri) and urea, and their combinations. In addition, intake, milk yield and composition of lactating dairy cows were evaluated. In the first experiment, eight different silages were made using the sugarcane cultivar IAC 86-2480 with the additives: Lactobacillus plantarum/Lactobacillus buchneri (strain NCIMB 40788), urea at the level of 0.5% of the original material and soybean hulls at 10 and 20% of the original fresh material. Eight treatments were tested in mini-silos: pure sugarcane (CN); sugarcane with bacterial inoculant (CNIB); sugarcane with 0.5% urea (CNUR); CNUR + IB (CNIBUR); CNUR + 10% soybean hulls (CNUR10%CS); CNUR + 20% soybean hulls (CNUR20%CS); CNIBUR + 10% CS (CNIBUR10% CS) and CNIBUR + 20% CS (CNIBUR20%CS). The experimental design was a completely randomized with 9 opening periods (1, 2, 3, 7, 15, 30, 60, 120 and 180 days post-closing) with three replicates. We evaluated total, gaseous, and effluent losses as well as the percentages of dry matter, crude protein, neutral detergent (NDF) and acid detergent fiber (ADF). There was no significant effect of bacterial innoculant or urea on silage characteristics: neither pH, dry matter content of silage or gaseous and effluent losses. Urea and bacterial inoculant increased the level of lactic acid and reduced ethanol level (P<0.05) of the silages. The addition of 10 or 20% of soy hulls, by the other side, led to an improvement of silage composition and reduced gaseous and effluent losses, but showed no effect on ethanol or lactic acid of the ensiled sugarcane. In the second experiment, we evaluate the performance of lactating cows fed sugarcane silages with and without soybean hulls or bacterial innoculant. Four lactating cows were randomly assigned to a 4x4 Latin Square design. The experimental treatments tested were: sugarcane silage with bacterial inoculant (CNIB), CNIB with 10% soybean hulls (CNIB10%CS) and CNIB with 20% CS (CNIB20%CS), and a control treatment without additive (CN) pure cane silage (CN). The four experimental periods, lasting 21 days, were splitted into 14 days of adaptation and the following seven days for data collection (milk yield and composition and live weight of the animals). Bacterial inoculant affected negatively dry matter, NDF and protein intake, whereas addition of soybean hulls increase intake of DM, NDF, milk yield and weight gain. The higher the level of soy hulls the higher gain in weight. The inclusion of soy hulls led to weight gain whereas CN or CNIB led to weight losses. It is recommended the addition of soy hulls to the sugarcane chopped material to be ensiled at levels from 10 to 20%.